The impact of macroeconomic changes on the Malaysian shariah stock index / Anita Md Shariff, Zuraida Mohamad and Syarafina Ismail - Md Shariff, Anita; Mohamad, Zuraida; Ismail, Syarafina (2017)
This paper seeks to explore the impact of four macroeconomic variables (i.e. interest rate, inflation rate, exchange rate and oil price) on the shariah stock prices in the Malaysian Stock Market. 50 sharia-compliant securities from the consumer product and property sectors listed at Bursa Malaysia are chosen. Six years panel data from 2010 to 2015 are analysed using STATA. A correlation analysis was carried out followed by Breusch Pagan Test and Random Effect (RE) model. Result reveals only three macroeconomic variables significantly impact the Shariah Stock prices. Interest rate and oil price positively impact while exchange rate negatively impacts the prices. Inflation rate does not have any significant impact on the sharia stock market performance. The result also shows that Sharia stock performance from the two sectors move in the opposite direction from that of the conventional stocks when facing with macroeconomic circumstances. It also provides evidence that Sharia stocks are perceived by investors as viable and safe investment alternatives during uncertain economic conditions.